Effects of three kinds of growth regulators on flowering and branch physiological characteristics of Paeonia rockii - LIU Jiamiao; TANG Hong; ZHU Jiachen; TAO Xuanlin; XUE Nana (Xibei zhiwu xuebao)
[Objective] The study aims to explore the effects of three kinds of growth regulators on the flowering and branch physiological characteristics of Paeonia rockii and to provide theoretical basis for the chemical regulation of flowering traits of P . rockii. [Methods] With ‘Xiangyabai’ from Guantangou P . rockii Cultivation Base in Yuzhong County, Lanzhou City, Gansu Province as the material, three kinds of growth regulators (IAA, GA3, and 6-BA) at concentrations of 100, 300 and 500 mg/L were sprayed on the leaves before flower bud differentiation, with water as the control. The changes of physiological indexes, including flowering at full-bloom stage, antioxidant enzyme activity, and osmotic adjustment substance content of branches, were investigated. [Results] Compared with the control, the three growth regulators increased the number of flowers and the rate of double-petal flowers to varying degrees, and the effect of 500 mg/L 6-BA treatment was the best. The SOD activity, POD activity, and Pro content of the single-petal branches and double-petal branches were the highest. The activities of SOD, POD, and CAT in the branches of P . rockii were positively correlated with the number of flowers and the rate of doublepetal flowers, which played an important role in the flowering process, with SOD was more prominent. The number of flowers, rate of double-petal flowers, and physiological indexes of the branches were the best under the treatment of 500 mg/L 6-BA, 500 mg/L GA3, and 300 mg/L GA3, respectively. [Conclusion] The three growth regulators directly or indirectly increased flowering number and stamen petaling degree of P . rockii through the physiological indexes of the branches, but there were differences in the degree of promotion, among which the number of flowering and the rate of double petaling of the 500 mg/L 6-BA treatment increased the most.